THE EFFECT OF LIQUIDITY, CAPITAL STRUCTURE, AND PROFITABILITY ON FIRM VALUE IN COSMETIC COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Wiguna, Raden Roro Dwi Rizky Pratiwi Rahayu; Suwaidi, Rahman Amrullah (Yayasan Education and Social Center, 2023)
Firm value is essential in the company because all company decisions can influence investor decisions. If the company value is good, investors and potential investors will view the company favorably, and vice versa. This study aims to determine the effect of liquidity, capital structure, and profitability on the value of companies listed on the Indonesia Stock Exchange in 2014 - 2021. The population used in this study is cosmetics companies listed on the Indonesia Stock Exchange in 2014 - 2021, totaling six companies. The research sample used a saturated sampling technique, where the population in this study was used as a sample. The data analysis technique in this study uses Multiple Regression Analysis. The results of this study prove that liquidity and profitability have a positive and significant effect on firm value. Capital structure negatively affects substantial value in cosmetic companies listed on the Indonesia Stock Exchange